'Duties In Aid of the Civil Power': The Deployment of the Army to Glasgow, 31 January to 17 February 1919. Issue 2 (November 2018) - Barclay, Gordon J.
Abstract : On 31 January 1919 a demonstration in Glasgow in support of an unofficial strike for a 40-hour working week descended into violence, the 'Battle of George Square', probably set off by an ill-judged police baton charge. Troops called by the Sheriff of Lanarkshire began to arrive late that evening, and six tanks arrived on the following Monday. The 'Battle' and the subsequent military deployment have entered the mythology of Scottish socialism and, more recently, of Scottish nationalism. The strike had an overtly political aim: to force the Government to step in to regulate industry. Many in government believed that it had a more profoundly political, or even revolutionary aim. No detailed account of the troop deployment has yet been written, and in this gap mythology has flourished. This paper is intended to fill that gap and to challenge the myths.